1991
DOI: 10.1007/bf00867327
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spelling-to-sound regularity on naming in French

Abstract: Summary. In two experiments the naming task was used to investigate the effect of spelling-to-sound regularity on performance for French words varying in frequency of usage. In both experiments the results showed a significant effect of regularity on naming latencies. Contrary to what has been found in previous experiments using English stimuli, the regularity effect did not vary as a function of word frequency. However, in both experiments significantly more errors, and specifically regularisation errors, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 15 publications
2
47
0
2
Order By: Relevance
“…However, the manipulation of regularity with multisyllabic words imposes additional constraint. Indeed, it has recently been reported that phonological translation was affected more by early than by late irregularities (Coltheart & Rastle, 1994;Content, 1991;Content & Peereman, 1992). The serial position of the irregular correspondence was determined for the unfamiliar words with frequent or rare enemies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the manipulation of regularity with multisyllabic words imposes additional constraint. Indeed, it has recently been reported that phonological translation was affected more by early than by late irregularities (Coltheart & Rastle, 1994;Content, 1991;Content & Peereman, 1992). The serial position of the irregular correspondence was determined for the unfamiliar words with frequent or rare enemies.…”
Section: Discussionmentioning
confidence: 99%
“…First, although exception words with frequent or rare enemies differed on naming latencies, they did not diverge on regularisation rates. If the items with frequent enemies were disadvantaged because of their early irregularities, then more regularisation errors should have occurred for these items than for those with rare enemies (see Content, 1991;Content & Peereman, 1992). Second, a post-hoc analysis was carried out to examine whether the RT difference between the items with frequent or rare enemies still persisted when both categories were matched on the irregularity position.…”
Section: Discussionmentioning
confidence: 99%
“…Psycholinguistic research indicates that word frequency (e.g., Balota & Chumbley, 1984;Frederiksen & Kroll, 1976;Hudson & Bergman, 1985; for a review, see Monsell, 1991) and grapheme-phoneme correspondence (GPC) consistency (e.g., Content, 1991;Content & Peereman, 1992;Jared, 1997;Peereman, 1995;Seidenberg, Waters, Barnes, & Tanenhaus, 1984;Ziegler, Perry, & Coltheart, 2003) affect the performance of skilled readers. However, GPC consistency has a greater impact than word frequency at the beginning of reading acquisition, probably because word-frequency effects are item-specific, unlike GPC consistency effects which depend on generalizations based on associations between frequent GPCs.…”
Section: Main Variables In the Study Of Literacy Acquisition: A Shortmentioning
confidence: 99%
“…Many studies have shown that print-tosound consistency influences reading performance (see Berent & Perfetti, 1995, for a review of the English data; Content, 1991;Content & Peereman, 1992;Peereman, 1995, for French). The notion of consistency refers to the variability of the phonological codes that can be assigned to a particular orthographic unit.…”
Section: Lexop Variablesmentioning
confidence: 99%